Intangibility and Productivity in Public Service Healthcare - Kaivo-oja, Jari; Kinder, Tony; Stenvall, Jari (University College of Economics and Cultur, 2026)
Purpose
The paper discusses the causes of rising costs and lowering productivity in healthcare systems.
Design / Methodology / Approach
OECD healthcare system data from six developed countries (the USA, Japan, France, the UK, Finland, and Sweden) is cleaned and structured. Sample selection is based on a mix of size and type of healthcare system. Data from published sources is used to cross-reference quantitative data analysis.
Findings
The paper challenges service management theory (Vargo & Lusch, 2004) and public service management theory, which argues that services are necessarily intangible, by showing that all services have a tangible element. The paper disputes Baumol’s (2012) cost disease theory (that service productivity necessarily declines with rising labour costs), arguing that the quality of service cannot be discounted, and taking healthcare as an example, that increasing deployment of tangible technologies enhances productivity, recognising that exogenous factors (rising cost of pharmaceuticals) are a drag on performance.
Originality / Value / Practical implications.
Our research question is: Does characterising public services as an intangible obfuscate the argument about their relative productivity. We conclude that basing the definition of services on intangibility obfuscates productivity. The paper concludes that the contingent element of intangibility in services is overemphasised and wrongly ascribes it as a necessary condition of public services since the person-to-person element remains pervasive and important in public services. In the SDL case of Vargo and Lusch (2007, 2017), we further conclude that ascribing logics to services, including their intangibility, suggests an uncontested meaning of services that does not exist, and in doing so subsumes agency and leadership of services by imputing a deterministic trajectory.